1982
DOI: 10.1037/h0077926
|View full text |Cite
|
Sign up to set email alerts
|

Role of retroactive interference in the spatial memory of normal rats and rats with hippocampal lesions.

Abstract: The importance of retroactive interference (RI) in memory for spatial locations was studied by using a 12-arm radial maze and a standard RI paradigm. Animals in the RI condition first learned to choose 4 of the 12 arms, followed by training to a second set of 4 arms. In the control condition for interference, rats learned the first set of arms but were not trained to approach the second set. Thereafter, animals in each interference condition were assigned to groups (hippocampal, cortical control, unoperated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
3

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
3
17
3
Order By: Relevance
“…On the other hand, Jarrard (1983;Jarrard & Elmes, 1982) reported results that do not agree with the present findings. Jarrard used a task similar to that used here-a radial-maze task with explicit working-memory and reference-memory components-and conducted in a similar experimental environment.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…On the other hand, Jarrard (1983;Jarrard & Elmes, 1982) reported results that do not agree with the present findings. Jarrard used a task similar to that used here-a radial-maze task with explicit working-memory and reference-memory components-and conducted in a similar experimental environment.…”
Section: Discussioncontrasting
confidence: 56%
“…A precise comparison of the extent of the lesions in the two studies is not possible. However, the discrepant findings may be attributable to differences in the extent of the hippocampal lesions, to differences in the amount of neocortical tissue damage (which is greater in the Jarrard, 1983, andJarrard &Elmes, 1982, experiments than in the present experiment), or to other differential effects of the two techniques.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Subsequent studies demonstrated that not only monkeys [11 ,12] but also pigeons [13,14] and rats [15][16][17][18][19] can also perform dualtasks in various conditions and also exhibit dual-task interference effects analogous to those in humans (Table 1). Recently, Smith et al [12] applied the dual-task method to examine whether or not metacognitive process can be dissociated from perceptual-level process using monkeys.…”
Section: Behavioral Analyses Of the Dual-task Interference Effect In mentioning
confidence: 94%
“…Combination of tasks Behavioral studies Moise [9] Monkey DMS a + simple reaction time task Washburn and Astur [10] Monkey DMS + overt OT b or numerical judgment task Basile and Hampton [11 ] Monkey DMS + motor, image perception, or image classification task Smith et al [12] Monkey DMS or DMP c + perceptual confidence judgment Kendrick and Rilling [13] Pigeon DMS + VI d , EXT e , or DRO f schedule Calder and White [14] Pigeon DMS + VI schedule Maki et al [15] Rat 8-arm WS g radial maze + 4-arm WS h radial maze Beatty and Shavalia [16] Rat 8-arm WS radial maze + 8-arm WS or WS radial maze Roberts [17] Rat 8-arm WS radial maze + 8-arm WS radial maze Cook and Brown [18] Rat 12-arm WS radial maze + 12-arm WS radial maze Jarrard and Elmes [19] Rat 12-arm WS radial maze + 4-arm WS radial maze Harper et al [45] Rat SPR i in 12-arm maze + food consumption Neurophysiological studies…”
Section: Speciesmentioning
confidence: 98%